The effects of recovery duration during high-intensity interval exercise on time spent at high rates of oxygen consumption, oxygen kinetics, and blood lactate - Smilios, I.; Myrkos, A.; Zafeiridis, A.; Toubekis, A.; Spassis, A.; Tokmakidis, S. P. (The Journal of Strength and Conditioning Research, 2018)
The recovery duration and the work-to-recovery ratio are important aspects to consider when designing a high-intensity aerobic interval exercise (HIIE). This study examined the effects of recovery duration on total exercise time performed above 80, 90, and 95% of maximum oxygen consumption (VO2max) and heart rate (HRmax) during a single-bout HIIE. We also evaluated the effects on VO2 and HR kinetics, blood lactate concentration, and rating of perceived exertion (RPE). Eleven moderately trained men (22.1 ± 1 year) executed, on 3 separate sessions, 4 × 4-minute runs at 90% of maximal aerobic velocity (MAV) with 2, 3, and 4 minutes of active recovery. Recovery duration did not affect the percentage of VO2max attained and the total exercise time above 80, 90, and 95% of VO2max. Exercise time above 80 and 90% of HRmax was longer with 2 and 3 minutes (p = 0.05) as compared with the 4-minute recovery. Oxygen uptake and HR amplitude were lower, mean response time slower (p = 0.05), and blood lactate and RPE higher with 2 minutes compared with 4-minute recovery (p = 0.05). In conclusion, aerobic metabolism attains its upper functional limits with either 2, or 3 or 4 minutes of recovery during the 4 × 4-minute HIIE; thus, all rest durations could be used for the enhancement of aerobic capacity in sports, fitness, and clinical settings. The short (2 minutes) compared with longer (4 minutes) recovery, however, evokes greater cardiovascular and metabolic stress and activates to a greater extent anaerobic glycolysis and hence, could be used by athletes to induce greater overall physiological challenge.